Long Non-Coding RNA AL139385.1 as a Novel Prognostic Biomarker in Lung Adenocarcinoma - Chen, Xi; Guo, Jishu; Zhou, Fan; Ren, Wenjun; Huang, Xiaobin; Pu, Jun; Niu, Xiaoqun; Jiang, Xiulin (Frontiers in Oncology, 2022)
Lung adenocarcinoma (LUAD) is the most common histological lung cancer, and it is the leading cause of cancer-related deaths worldwide. LncRNA-AL139385.1 (ENSG00000275880) is a novel lncRNA that is abnormally expressed in various cancer types including LUAD. However, the underlying biological function and potential mechanisms of AL139385.1 driving the progression of lung adenocarcinoma remains unclear. In this study, we investigated the role of AL139385.1 in lung adenocarcinoma and found that DNA hypomethylation was positively correlated with AL139385.1 expression in LUAD. Moreover, we uncover that the expression of AL139385.1 in LUAD tissues was significantly higher than that of AL139385.1 expression in adjacent normal tissues. Kaplan-Meier survival analysis showed that patients with higher AL139385.1 expression correlated with adverse overall survival and progression-free survival. ROC curve analysis showed that the AUC value of AL139385.1 was 0.808. Correlation analysis showed that AL139385.1 expression was associated with immune infiltration in LUAD. We also found that AL139385.1 was upregulated in LUAD cancer tissues and cell lines. Knock down of AL139385.1 significantly inhibited cell proliferation and migration abilities of LUAD. Finally, we constructed a ceRNA network that including hsa-miR-532-5p and four mRNAs (GALNT3, CYCS, EIF5A, and ITGB4) specific to AL139385.1 in LUAD. Subsequent Kaplan-Meier survival analysis suggested that GALNT3, CYCS, EIF5A, and ITGB4, were potential prognostic biomarkers for LUAD patients. In conclusion, this finding provide possible mechanisms underlying the abnormal upregulation of AL139385.1 as well as a comprehensive view of the AL139385.1-mediated ceRNA network in LUAD, thereby highlighting its potential role in diagnosis and therapy. Keywords: AL139385.1, lung adenocarcinoma, prognosis biomarker, DNA methylation, ceRNA, cell proliferation, cell migration